Depression scores correlate with glycosylated hemoglobin A levels in type 2 diabetics from a Mayan community - Góngora-Alfaro, José L.; Solís-Díaz, Luis Alberto; Álvarez-Cervera, Fernando José (Horizonte Sanitario, 2022)
Objective: To assess whether depression and quality of life scores correlate with glycosylated hemoglobin A (HbA1c) levels in type 2 diabetes mellitus (T2DM) patients of predominant Mayan ethnicity, from a rural community in the state of Yucatán, Mexico. Materials and methods: Instruments: for depression, CES-D (cutoff ≥ 16); for quality of life, D-39; criterion for poor glycemic control, HbA1c ≥ 8%. Results: Depression was detected in 36.3% of 33 diabetic subjects (10 men, 23 women), and their HbA1c levels (mean ± SD) were higher (10.7 ± 2.5%) than for those without depression (8.6 ± 2.2%, p = 0.015; unpaired Student’s t-test, two-tailed). Depression occurred in 33.3% of diabetics with HbA1c ≥8%, but only in 3.0% of those with HbA1c < 8% (p = 0.027, Fisher’s exact test). HbA1c levels positively correlated with CES-D scores (r2 =0.135; p = 0.035; Pearson). D-39 “Anxiety-Worry” (AW) dimension scores were higher in diabetics with depression (43.3 ± 22.2) than in those without depression (17.7 ± 17.8; p = 0.005, Mann-Whitney U-test). A positive correlation was found between CES-D and AW scores (r2 = 0.304; p = 0.001; Pearson). Conclusions: Considering that depression and anxiety have been related to poor self-care for achieving a good glycemic control, we propose the concomitant use of CES-D and D-39, which are validated and easy-to-apply instruments, as screening tests to detect depression and anxiety in T2DM patients residing in rural communities. Therefore, if patients test positive on one or both instruments, they can be referred to a psychiatrist to confirm the diagnosis and provide appropriate therapy. This would help to promote adherence to diabetes control measures and improve their quality of life. Key words: Diabetes Mellitus, Type 2; Depression; Anxiety; Glycosylated hemoglobin A